Call quality monitoring for VoIP - Bayley, T.; Rohani, B.; Johansson, A.; Caldera, Manora; Zepernick, H. (2011)
A method of monitoring the speech quality of a Voice-over-IP call is described in this paper. This method is attractive because it employs the ITU-T standard P.862 for Perceptual Evaluation of Speech Quality which is well-known for its accuracy. In addition, with the proposed method, call quality is monitored without interfering with the call while it is in progress. The results corresponding to an implementation of this method shows call quality can be measured with excellent accuracy under typical network delays. © 2011 IEEE.